2001
DOI: 10.1002/hec.599
|View full text |Cite
|
Sign up to set email alerts
|

Private and social time preferences for health and money: an empirical estimation

Abstract: The main objective of this paper is to examine the relationship between individual time preference for health and money. To that end, we tested whether individuals discount their own health at the same rate as their own money and, similarly, whether they discount social health in the same terms as social money. To offer private and social money and health choices is, to the best of our knowledge, new in the literature on the estimation of time preferences and, in our view, represents a valid way in which to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 17 publications
(22 reference statements)
3
23
1
Order By: Relevance
“…Fuchs (1982) first provided empirical evidence on the links between time preference, health status, and schooling. Other studies by Shoda et al (1990), Olsen (1993), van der Pol and Cairns (2000), Lazaro et al (2001), Kirby et al (2002), Khwaja et al (2007), Asenso-Boadi et al (2008), and Chao et al (2009) have also reported that education and health affect patience.…”
Section: Notesmentioning
confidence: 87%
“…Fuchs (1982) first provided empirical evidence on the links between time preference, health status, and schooling. Other studies by Shoda et al (1990), Olsen (1993), van der Pol and Cairns (2000), Lazaro et al (2001), Kirby et al (2002), Khwaja et al (2007), Asenso-Boadi et al (2008), and Chao et al (2009) have also reported that education and health affect patience.…”
Section: Notesmentioning
confidence: 87%
“…When making public policy decisions, the social discount rate is usually regarded as an appropriate measure to use (Drummond et al 1987;Olsen 1993). Some studies have shown that discount rates for health were higher than those for money in both the social and private context (Lazaro et al 2001, although more recent evidence indicates that social time discount rates for health were lower than social time discount rates for money (Meerding et al 2010). As Cairns (2001) points out, the differences could be attributed to differing sample populations or differing methods of framing time preference.…”
Section: Societal and Private Time Discount Ratesmentioning
confidence: 99%
“…3 Examples of this approach can be found in Barsky et al (1997), Donkers et al (2001), Hartog et al (2002), Guiso and Paiella (2006) and Dohmen et al (2006). 4 For example Trostel and Taylor (2001) estimate time preferences using a consumption smoothing model while Benzion et al (1989), Coller and Williams (1999), Read (2001), Anderhub et al (2001) and Harrison et al (2002) use experiments and Barsky et al (1997), Donkers and van Soest (1999), Lazaro et al (2001) and Kapteyn and Teppa (2003) use hypothetical questions.…”
mentioning
confidence: 99%